Adoption of mobile learning among university students during and after the covid-19 pandemic in Bangladesh - Noor, Nazneen R (Jurnal Inovasi Teknologi Pendidikan, 2024)
Limited research has been done about the adoption of mobile learning among Bangladeshi university students, including those from public, private, and national universities. This study aims to unravel the nuances in students' attitudes influenced by personal and institutional factors, investigating the diverse higher education landscape post-return to traditional classrooms. The survey, encompassing demographic data and mobile technology utilization pre-, during, and post-COVID-19 from 453 Bangladeshi university students, is analyzed to measure their perceptions and attitudes regarding the efficacy of mobile learning. The result varies between public, private, and national university students. While many students have complimented and appreciated mobile learning for its ability to assist with financial struggles, the learning process, and grades, many of them have also reported a decline in the quality of their education during M-learning. Several students have expressed difficulty communicating and concentrating during online sessions. The study suggests that incorporating mobile learning technologies into traditional classroom settings could improve teaching and learning. Further research is needed to understand the impact of institutions on online education acceptance and student perceptions.